DOI: 10.31274/rtd-180816-5026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individualized instruction on the achievement of cognitive and affective objectives by selected first-year algebra students

Abstract: high schools. One class in each school was randomly selected as a treatment group and followed the individualized instruction procedures described as Individually Diagnosed and Prescribed. The other two classes served as control groups and were taught by a traditional lecture-discussion method. The same teacher taught both classes in each school. The study was limited to one academic year, 1973-74, when the students were in ninth grade. Participation in the study was restricted to those students who selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although teachers using this method have done an adequate job of teaching mathematics to many students, it is not ideally suited to teaching mathematics to the individual" (Farrell, 1980, p. 3). Farrell (1980) indicated that lecture is not a good method of teaching for the following reasons:…”
Section: Disadvantages;mentioning
confidence: 99%
“…Although teachers using this method have done an adequate job of teaching mathematics to many students, it is not ideally suited to teaching mathematics to the individual" (Farrell, 1980, p. 3). Farrell (1980) indicated that lecture is not a good method of teaching for the following reasons:…”
Section: Disadvantages;mentioning
confidence: 99%